Use of Social Networking Websites as an emerging Marcom tool - Bansal, Harbhajan; Bharti, Charu (Gyan Management Journal, 2015)
It is no exaggeration to say that marketing is undergoing a paradigm shift, in large part, to the Internet  and social media and social networks. The evidence is everywhere, for example, many consumers no  longer look up items in the Yellow pages; they search for them on the Internet. Using Social Networking  Websites, as marketing tool, is more than just marketing because it includes requires the development  of relationships based on shared interests.  We are still in early stages of the transformation social media and social networking is having on  marketing. Traditional marketing is undergoing a transformation due, in large part, to the Internet  and social networks and social media.  While social networking has gone on almost as long as societies themselves have existed, the  unparalleled potential of the Internet to promote such connections is only now being fully recognized  and exploited, through Web-based groups established for that purpose. With two thirds of the world's internet population visiting a social network or blogging website, and  the sector now accounting for over 10% of all internet time, websites such as Facebook, Linked In and  Twitter are channels that marketers can really tap into. Social networking can be an excellent way to acquire new customers and retain existing ones. The real  value is the way marketers can engage with their audience on a personal level. Instead of simply 'sell  sell sell', social networking is about the kind of two-way communication which helps to build a long  term relationship. Of course, this form of interaction may not be suitable for all brands, but many  organizations are benefittingfrom making their brand more personable.  This Paper analyses the opinion of potential consumer, that is the internet users, on their attitude  towards Social Networking Websites {SNWs) to be used as a Marcom tool (Marketing Communication  tool). The Study is based on Survey conducted where the opinions of the "Internet users" have been  collected, with a Sample Size of approx. 300, using 'Questionnaire' as a Research Tool. The Findings are  based on the data collected by survey. The recommendations have been given on the basis of Findings.
Keywords: Websites; transformation; networks; Facebook; Linked; Twitter; benefittingfrom